Management, and decision-making tool for data of multiple photovoltaic microgenerators distributed in Brazil - Antoniolli, Andrigo Filippo Gonçalves (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Civil, Florianópolis, 2022.